KAJIAN PEMERATAAN KESEMPATAN MEMPEROLEH PENDIDIKAN ANTAR KABUPATEN DI PROVINSI SUMATERA SELATAN TAHUN 2005 - Retnaningsih, Ekowati (Publikasi Penelitian Terapan dan Kebijakan, 2008)
Intervention to the education sector represent the Law recommendation which is in line with world agreement in target of Millennium Development Goals (MDGs), and it will double affect are improve the IPM and at one blow reach the MDGs. This Study was executed in the year 2006, using quantitative paradigm with the descriptive analysis. Source of Data used secondary data from on institution of South Sumatra province at 2004 / 2005. Study result indicate that in the year 2004 / 2005: SD/MI in South Sumatra Province have the APK was 106,97%, APM was 90,78%. At level SMP/MTS have APK was 71,58% and APM was 54,62%. Transition Number was 78,0%. Disparities of performance of generalization of education opportunity (APM) at SD/MI, SMP/MTS usher the district. Disparities of performance of generalization of education opportunity ( AT) of SMP/MTS usher the district. Recommendations to increase opportunity get education at level SD/MI and SMP/MTS are:1) Study use more variable and source of primary data so that its result will be more be comprehensive 2) Policy of program mush conduct more local specific because at the province level do not see the existence of influence of one of or some factor manifestly. Factor influence the equality education at level SD/MI more variation usher district.